The Microbiome-Mitochondria Dance in Prodromal Parkinson’s Disease - Cardoso, Sandra M.; Empadinhas, Nuno (Frontiers in Physiology, 2018)
The brain is an immunologically active organ where neurons and glia cells orchestrate complex innate immune responses against infections and injuries. Neuronal responses involve Toll-like or Nod-like receptors and the secretion of antimicrobial peptides and cytokines. The endosymbiotic theory for the evolutionary origin of mitochondria from primitive bacteria, suggests that they may have also retained the capacity to activate neuronal innate immunity. In fact, it was shown that mitochondrial damage-associated molecular patterns could signal and activate innate immunity and inflammation. Moreover, the mitochondrial cascade hypothesis for sporadic Parkinson’s disease (PD) argues that altered mitochondrial metabolism and function can drive neurodegeneration. Additionally, a neuroinflammatory signature with increased levels of pro-inflammatory mediators in PD affected brain areas was recently detected. Herein, we propose that a cascade of events initiating in a dysbiotic gut microbiome drive the production of toxins or antibiotics that target and damage mitochondria. This in turn activates neuronal innate immunity and triggers sterile inflammation phenomena that culminate in the neurodegenerative processes observed in the enteric and in the central nervous systems and that ultimately lead to Parkinson’s Disease.